Complications of leadless vs conventional (lead) artificial pacemakers - a retrospective review - Yasar Sattar; Waqas Ullah; Sohaib Roomi; Hiba Rauf; Maryam Mukhtar; Asrar Ahmad; Zain Ali; Muhammad Shan-; M Chadi Alraies (Greater Baltimore Medical Center, 2020)
Background: Leadless pacemakers (LPM) are introduced in cardiovascular market with a goal to avoid lead- and pocket-associated complications due to conventional artificial pacemakers (CPM). The comparison of LPM and CPM complications is not well studied at a case by case level. Methods: Comprehensive literature was searched on multiple databases performed from inception to December 2019 and revealed 204 cases that received LPM with a comparison of CPM. The data of complications were extracted, screened by independent authors and analyzed using IBM SPSS Statistics for Windows, Version 22.0 (Armonk, NY: IBM Corp.). Results: The complications of CPM were high in comparison to LPM in terms of electrode dislodgement (56% vs 7% of cases, p-value < .0001), pocket site infection rate (16% vs 3.4%, p-value = 0.02), and a lead fracture rate (8% vs 0%, p-value = 0.04). LPMs had a statistically non-significant two-times high risk of pericardial effusion (8%) compared to CPMs (4%) with a p-value = 0.8. Conclusion: LPMs appear to have a better safety profile than CPMs. There was a low pocket site and lead-related infections in LPM as compared to CPM. However, LPM can have twice the risk of pericardial effusion than CPMs, but this was not statistically significant.